Influence of the addition of strawberry guava (Psidium cattleianum) pulp on the content of bioactive compounds in kombuchas with yerba mate (Ilex paraguariensis) - WANDERLEY, Bruna Rafaela da Silva Monteiro; LIMA, Maria Eduarda Costa de; OLIVEIRA, Amanda Kaiane da Silva; SARTORI, Giliani Veloso; STROSCHEIN, Marcos Roberto Dobler; AMBONI, Renata Dias Mello de Castanho; FRITZEN-FREIRE, Carlise Beddin; AQUINO, Ana Carolina Moura de Sena (Food Science and Technology, 2023)
Kombucha is a beverage obtained by fermenting tea with a symbiotic culture of bacteria and yeasts. It has been investigated to explore less-used raw materials added to kombucha to partially replace tea and flavor the drink. This influences the sensory characteristics and the concentration of bioactive compounds. In this context, this study aimed to evaluate the influence of adding strawberry guava pulp on the total phenolic compound (TPC) content and in vitro antioxidant capacity of kombuchas made with green tea and yerba mate. Thus, it was observed that the fermentative process resulted in increased TPC content in the formulations made with green tea (T1) and with green tea and yerba mate (1:1) (T3). Furthermore, these formulations flavored with strawberry guava pulp presented the highest TPC contents [184.39 and 150.78 mg gallic acid equivalent (GAE)/100 mL, respectively]. Furthermore, the formulation T1 showed a high antioxidant capacity for ABTS+ and 2,2-diphenyl-1-picrylhydrazyl (DPPH) methods. On the contrary, the formulation T3 added with strawberry guava pulp showed the highest antioxidant capacity (5.24 µM TEAC/mL) by the ferric reductive antioxidant potential (FRAP) method. Thus, the strawberry guava pulp proved to be a promising alternative for the flavoring and diversification of kombuchas.